Emerging Trends in Peripheral Artery Disease: A Review of Recent Studies: A Literature Review - Zelda Rizkylia Meidinar Ardis; Agastya, Wayan Dhea (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Abstract Background. Peripheral artery disease (PAD) is a chronic vascular condition characterized by the narrowing or blockage of peripheral arteries, primarily affecting the lower extremities. It is a major manifestation of atherosclerosis and a significant contributor to cardiovascular morbidity and mortality worldwide. The disease disproportionately affects older adults, smokers, individuals with diabetes, and those with a history of hypertension or hyperlipidemia. Methods. Existing scholarly work was explored through PubMed, Google Scholar, and Scopus, using relevant keywords, such as